2018
DOI: 10.1097/mnm.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced computed tomography does not improve the diagnostic value of parathyroid dual-phase MIBI SPECT/CT

Abstract: Late CE-CT, compared with late LD-CT, did not significantly improve the sensitivity of dual-phase Tc-99m MIBI parathyroid SPECT/CT in a population of patients with primary hyperparathyroidism. These findings were consistent regardless of the size, location, or histology of the adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Although 99m Tc-MIBI SPECT/CT has high sensitivity and performs well in locating ectopic parathyroid, its sensitivity for parathyroid hyperplasia is only 60%, much lower than that of cervical ultrasound (87.5%). It also suggests that 99m Tc-MIBI SPECT/CT is less sensitive to parathyroid hyperplasia than parathyroid adenoma, which is in good accordance with previous studies [ 22 , 25 ]. Torregrosa et al have found that, in secondary hyperparathyroidism, the uptake of 99m Tc-MIBI is correlated with the cell cycle phases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although 99m Tc-MIBI SPECT/CT has high sensitivity and performs well in locating ectopic parathyroid, its sensitivity for parathyroid hyperplasia is only 60%, much lower than that of cervical ultrasound (87.5%). It also suggests that 99m Tc-MIBI SPECT/CT is less sensitive to parathyroid hyperplasia than parathyroid adenoma, which is in good accordance with previous studies [ 22 , 25 ]. Torregrosa et al have found that, in secondary hyperparathyroidism, the uptake of 99m Tc-MIBI is correlated with the cell cycle phases.…”
Section: Discussionsupporting
confidence: 92%
“…Stack et al found that parathyroid adenomas that weigh more than 350 mg are optimum for visualization by 99m Tc-MIBI SPECT/CT [ 24 ]. In addition, the sensitivity of 99m Tc-MIBI SPECT/CT could reach 92% when the weight of parathyroid adenoma is greater than 500 mg, and it decreased significantly to 64% in those lesions weighing less than 500 mg [ 25 ]. However, the weight of the lesion was not measured in our study; we only bring the length of the lesion as an indicator, which is easier to use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc-MIBI SPECT/CT, as a classical nuclear medical imaging technique, is often used for preoperative localization in patients with SHPT [ 14 , 15 ]. In our study, as shown in Table 2 , the sensitivity of 99m Tc-MIBI SPECT/CT was higher than that of 99m Tc-MIBI planar scintigraphy and US in SHPT based on lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Since 99m Tc-MIBI SPECT/CT shows advantages in preoperative localization and anatomical depiction, its application is currently increasing in popularity [14,15]. On 99m Tc-MIBI SPECT/CT images, the size, accurate location, density and adjacent tissues of the lesions can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective clinical study, Sandqvist et al 2019 reported a statistically significant increase in PTA localisation sensitivity when contrast-enhanced CT image sets [A + V] were added to [S + N] [2]. Andersen et al 2018 found no differences in sensitivity between [S + N] and [S + N + V] [3]. Finally, Yeh et al 2019 showed no differences in diagnostic performance after adding [S] to a [N + A + V] image protocol [4].…”
Section: Introductionmentioning
confidence: 99%